Identities Hidden in Challenges: The Sequential Mediation of Thriving at Work and Employee Investment - Saleem, Sharjeel; Humayun, Shazia; Latif, Bilal; Iftikhar, Umer; Sharif, Imran (Frontiers in Psychology, 2020)
The present study explores the influence of challenge stressors on identity orientation directly and via thriving at work and employee investment. Drawing on the broaden-and-build theory of positive emotions, this study proposes challenge stressors as a critical predictor of identity orientation. The purpose of this paper is to explore if a particular identity is salient in different contextual factors, and this study suggests that challenge stressors stimulate personal, relational, and collective identities to respond to a situation. The relationships hypothesized in this study were tested using a sample of 225 employees from the banking sector of Pakistan. A time-lagged research design consisting of two waves of data collection was employed. Structural equation modeling technique was used to test the hypotheses regarding the relationship between challenge stressors and identity orientation, including the role of thriving at work and employee investment as intervening mechanisms of this relationship. Results showed that challenge stressors had a significant positive relationship with identity orientation. The results also confirmed the sequential mediation of thriving at work and employee investment in the relationship between challenge stressors and identity orientation. The findings suggest that the positive side of stress as a strength motivates employees for continued self-development. Importantly, challenge stressors enhance employees’ thriving at work and, in turn, they invest in the work more and identify themselves strongly with their organization and work.